State of the Art of Virtual Reality Simulation Technology and Its Applications in 2005 - Stothard, Phillip; Galvin, J. (School of Mining Engineering, University of New South Wales, 2005)
The School of Mining Engineering at the University of New South Wales (UNSW) has been developing immersive, interactive computer-based training simulators for a number of years with research funding provided by Coal Services (CS), the Australian Coal Association Research Program (ACARP) and the Australian Research Council (ARC). The virtual reality(VR) simulators are being developed to improve the effectiveness of training in the Australian coal mining industry with a view to enhancing health and safety. VR theatres have been established at UNSW and at the Newcastle Mines Rescue Station (NMRS).A range of experienced and inexperienced mining personnel has already had the opportunity to train in them. A capability in immersive, interactive virtual reality training has been established and the reaction to the new technology has been positive and confirmed the benefits to be gained in going to the next stage in developing this capability. Given the significant advances in computer technology that have occurred since this research was initiated at UNSW, it was considered wise to undertake a study of the ‘State of the Art of Virtual Reality Simulation Technology and Its Application in 2005’. This should enable nformed decisions to be made on technologies and techniques that could further enhance the simulators and give insight into how the existing VR capability at UNSW can be placed on a sustainable foundation. This Research Overview summarises the findings of the study. It recommends the continued development and testing of the simulators towards a system that presents the users with hi-fidelity imagery and function that is based on 3D models, developed using real mine plans, safety data and manufacturer’s drawings. The simulators should remain modular in design, such that equipment can be updated and added easily over time. Different mine training scenarios and models based on sound educational principles should be developed with major input from experienced mining industry personnel. The simulations that have been developed, that is, Self-Escape, Rib Stability and Sprains and Strains should also continue to be developed and refined. The study has confirmed that such simulations are a powerful visualisation and training tool for enhancing the understanding of mine safety procedures and operations in the coal mining industry. This Scoping Study was undertaken with funding provided from the JCB Health and Safety Trust administered by Coal Services Pty Limited. The support of the Trust and trustees is gratefully acknowledged. The contributors of information are also gratefully acknowledged.